2006
DOI: 10.1089/aid.2006.22.52
|View full text |Cite
|
Sign up to set email alerts
|

Detection of T Lymphocytes Specific for Human Endogenous Retrovirus K (HERV-K) in Patients with Seminoma

Abstract: Human endogenous retrovirus K (HERV-K) is distinctive among the retroviruses that comprise about 8% of the human genome in that multiple HERV-K proviruses encode full-length viral proteins, and many HERV-K proviruses formed during recent human evolution. HERV-K gag proteins are found in the cytoplasm of primary tumor cells of patients with seminoma. We identified HERV-K-specific T cells in patients with a past history of seminoma using the interferon-gamma ELISPOT assay and an MHC-HERV-K peptide-specific tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 57 publications
0
53
0
3
Order By: Relevance
“…Moreover, immune responses to endogenous retrovirus derived proteins have also been correlated to cancer (20,21,23,46), but no clear clinical significance has yet been suggested. Here, we identify an HERV-K GAG protein, located on chromosome 22q11.23, highly expressed in prostate cancer and capable of generating a specific immune response in advanced stages of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, immune responses to endogenous retrovirus derived proteins have also been correlated to cancer (20,21,23,46), but no clear clinical significance has yet been suggested. Here, we identify an HERV-K GAG protein, located on chromosome 22q11.23, highly expressed in prostate cancer and capable of generating a specific immune response in advanced stages of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Specific immune response to endogenous retrovirus components is well described in the field (20,21,23,46), but no clear correlation to cancer progression has yet been determined. In this work, we showed that patients with advanced prostate cancer have a higher incidence of humoral immune response to GAG-HERV-K protein, suggesting an increase in gene expression due to prostate cancer progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, CTLs recognizing HERV-K-derived peptides that kill tumor cells in vitro have been identified in a few cancer patients (12,14). Similarly, we isolated and expanded a T cell clone from the blood of a responding transplant patient that recognized an HERV-E-derived antigen and killed patient RCC cells and HLA-A11 + RCC cells in vitro.…”
Section: Figurementioning
confidence: 99%
“…However, recent studies have revealed that at least some members of the transposable element families are transcriptionally active and may be capable of causing human cancers through several mechanisms. The association of transposable elements with breast cancer (Wang-Johanning et al, 2003b), melanoma (Buscher et al, 2005), seminoma (Rakoff-Nahoum et al, 2006), germ cell tumors (Galli et al, 2005), leukemia (Depil et al, 2002), ovarian carcinomas (Menendez et al, 2004), and prostate adenocarcinoma (Wang-Johanning et al, 2003a) has been suggested. Therefore, transposable elements may play a biological role in cancer development or organismal complexity by introducing transcriptional diversity .…”
Section: Introductionmentioning
confidence: 99%